2022
DOI: 10.1108/lodj-04-2021-0146
|View full text |Cite
|
Sign up to set email alerts
|

How servant leadership affects organizational citizenship behavior: the mediating roles of perceived procedural justice and trust

Abstract: PurposeThe paper aimed (1) to examine the mediating effects of procedural justice perception and trust in leaders between servant leadership and customer-oriented organizational citizenship behavior and (2) to investigate the relationships between procedural justice perception and trust in leaders in the context of Chinese hotel industry.Design/methodology/approachThe paper opted for a quantitative study using online survey to collect data. Data screening was carried out to ensure all the data met the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 94 publications
(138 reference statements)
3
29
0
3
Order By: Relevance
“…Research depicts that leadership styles such as transformational, transactional, servant and leader-member exchange have a positive impact on OCB [11][12][13][14][15]. Moreover, the studies have reported a significant positive relationship between servant leadership and employee OCB [16][17][18][19][20][21]. When leaders act with humility which is one of the important aspects of level 5 leader, they tend to build trust among employees and employees put an extra effort in their jobs.…”
Section: Introductionmentioning
confidence: 99%
“…Research depicts that leadership styles such as transformational, transactional, servant and leader-member exchange have a positive impact on OCB [11][12][13][14][15]. Moreover, the studies have reported a significant positive relationship between servant leadership and employee OCB [16][17][18][19][20][21]. When leaders act with humility which is one of the important aspects of level 5 leader, they tend to build trust among employees and employees put an extra effort in their jobs.…”
Section: Introductionmentioning
confidence: 99%
“…Employees will notice that service culture necessitates behaviors that go beyond formal requirements in business environment, which will probably lead to a greater OCB inside their workgroup (Walumbwa et al, 2010). By serving them or changing their surroundings, servant leaders can reinforce workers' motivation, capacity, or the chance to exhibit OCB (Qiu & Dooley, 2022;Greenleaf, 1998). Furthermore, OCB can function as a mechanism that connects leadership behaviors and employee creativity, because OCB tends to be fostered through servant leadership, which leads to knowledge exchange among employees.…”
Section: Servant Leadershipmentioning
confidence: 99%
“…According the studies of ref. [8,[25][26][27][28][29][30], organizational justice has a significant relationship with organizational citizenship behaviors of employees. The following hypotheses can be advanced based on previous research's theoretical foundation: H1: Organizational justice has a positive and significant impact on sustainable organizational citizenship behavior.…”
Section: Organizational Justice and Sustainable Organizational Citize...mentioning
confidence: 99%
“…According to the studies of ref. [8,[25][26][27][28][29][30] organizational justice (OJ) has a positive and significant effect on Sustainable organizational citizenship behavior (SOCB) (see Table 3).…”
Section: Organizational Justice (Oj) and Sustainable Citizenship Beha...mentioning
confidence: 99%